Differential average daily gain of pregnant Holstein × Gyr heifers: effects on future milk production and performance of their calves - Oliveira Neto, Antônio Paulo de (2024)
This study assessed the effects of different average daily gains (ADG) during pregnancy on the growth, nutrient digestibility, milk production, composition, and metabolism of dairy heifers, as well as the performance of their offspring. Twenty Holstein × Gir heifers, averaging 420 ± 15.0 kg in body weight and 18 ± 3.9 months in age, were randomly assigned to two treatment groups: a moderate ADG of 0.37 kg (MOD, n = 10) and a high ADG of 0.72 kg (HIG, n = 10). These heifers subsequently produced sixteen 3/4 Holstein × 1/4 Gyr calves. The heifers were fed a total mixed ration twice daily from the 70th day of pregnancy until calving. Calves were provided with colostrum constituting 15% of body weight with a minimum Brix of 25%, 6 L of transition milk for the first two days, followed by the same volume of raw milk daily until weaning. From day three onwards, calves had ad libitum access to a starter (DM 87.8%, CP 19.6%, starch 44.8%) and were introduced to hay (Cynodon dactylon) at 40 days. Data collection occurred over five periods (feed, feces, urine, and blood), each lasting five days starting from 100 days of gestation and occurring at 30-day intervals. Calves were monitored from birth to weaning with morphometric measurements, body weight, and blood collections on days 1, 31, 61, and 91, alongside daily collections of concentrate and hay and their leftovers. Results indicated that the MOD and HIG heifers had increasing intakes of dry matter, organic matter, crude protein, starch, and neutral detergent fiber throughout pregnancy. Nutrient digestibility did not differ between the MOD and HIG groups. However, there was a significant interaction for nitrogen of microbial origin (N-mic), which was higher in MOD heifers during the 4th and 5th months of pregnancy. Milk production over 305 days and milk corrected for 4% fat showed no differences between the ADG groups. The MOD heifers produced milk with a higher fat percentage, although protein percentages were similar between groups. Total solids were higher in the MOD group. Hormone and metabolite levels showed no interactions between treatments and lactation time, except for triiodothyronine, which was higher in the HIG group during the 4th and 9th months. No differences were observed in the ADG of calves from both groups at any evaluated times (31, 61, and 91 days). Calves from the MOD group exhibited compensatory growth, performing well from birth to weaning despite the lower nutritional intake of their mothers during gestation. In conclusion, a moderate ADG during pregnancy in 5/8 Holstein × Gyr heifers did not affect nutrient digestibility or milk production but resulted in higher milk fat content. Key words: fetal programming, Holstein × Gyr, milk production, nutrition, performance.